Adsorption of Tetracycline on the Bauxite and Modified Bauxite at Different Temperatures - Radhi, Israa M.; Mohammed, Yousif I.; Himdan, Takialdin A.; Badri, Dhefaf H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study, bauxite and modified bauxite /polymer, which were prepared as an adsorbent surfaces to adsorption of the tetracycline from aqueous solutions. A series of adsorption experiments were conducted to determine the equilibrium time and temperature effect on the adsorption process. The results showed that adsorption was agreed with the Freundlich equation model for the surface of the bauxite. As for the modified bauxite surface, the results were consistent with the Langmuir equation model. The values of the basic thermodynamic functions of the adsorption process were calculated, so the process of adsorption was founded spontaneous and endothermi